105 A case of resolving, levodopa responsive, asymmetric Parkinsonism. Issue 3 (9th February 2012) - Muhammed, K; Bain, P
Abstract : Sodium valproate has been reported to induce action and less frequently rest tremor. We describe an unusual case that demonstrates that sodium valproate induced unilateral Parkinsonism that appeared to respond to levodopa. Furthermore, the Parkinsonian inducing effects of sodium valproate took 9 years to resolve after its withdrawal: A 69-year-old lady presented with a 2-year history of left sided Jacksonian seizures. Initially a conservative management approach was implemented because of her mild motor deficits and sodium valproate commenced. Three years later she had a broadly symmetrical rest and action tremor of the arms. She also had clear signs of right sided Parkinsonism, ipsilateral to her right frontal para-falcine meningioma. Although sodium valproate was thought to be responsible for the symmetric rest and action tremor it seemed improbable that it had also caused unilateral Parkinsonism. Consequently, the patient was thought to have developed idiopathic Parkinson's disease (PD) and co-careldopa commenced. After withdrawal of sodium valproate and on treatment with co-careldopa the patient's left sided rest tremor resolved. After resection of the meningioma the right sided rest tremor disappeared. Over the next 7 years mild Parkinsonian signs remained, in spite of treatment with co-careldopa, suggesting that the patient had PD as the adverse effects of sodium valproate would have been expected to have dissipated. However, the non-progressive nature of the patient's Parkinsonism prompted a 123I-FP-CIT SPECT scan. This was normal, excluding PD and suggesting that the patient's Parkinsonism had in deed been drug induced.